EVALUATION OF RISK MANAGEMENT STRATEGIES IN PROFIT OPTIMIZATION IN THE BANKING SECTOR - Adhista Setyarini; Ziko Hamdi; Mohd Syahrin (CV. Adiba Aisha Amira, 2025)
This study aims to evaluate risk management strategies in profit optimization efforts in the banking sector. The findings reveal that the implementation of a reliable risk management strategy is able to contribute significantly to increasing profitability and financial stability of banks. Solid risk management helps in identifying, measuring, and managing various potential risks that could potentially threaten the bank's financial performance. Successful risk management enables banks to minimize potential losses and maximize opportunities, ultimately increasing profits in a sustainable manner. This study confirms the importance of integrating risk management into a bank's business strategy. Risk management is not only needed as a protection tool, but also as an important component in strategic decision-making. By incorporating risk considerations in day-to-day activities, banks can make more informed and timely decisions, which in turn helps reduce uncertainty and improve operational efficiency. The role of technology and data analytics is also highlighted, as it improves the accuracy of risk prediction and evaluation. The utilization of advanced technology enables banks to respond to risks quickly and effectively, thereby preventing negative impacts on financial performance. The implementation of technology-based risk management systems enhances transparency and accountability, which increases stakeholder confidence in bank management. In addition, compliance with dynamic regulations is also an important factor in the risk management strategy. Stringent regulations encourage banks to continuously adapt and refine their risk management framework. Compliance with regulatory rules not only avoids sanctions but also builds a good reputation in the eyes of investors and customers.